2014
DOI: 10.1589/jpts.26.1219
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Short-term Aquatic Training on Obstacle Crossing in Gait by the Elderly

Abstract: [Purpose] The purpose of this study was to examine the fall-prevention effect of 12 weeks of aquatic training for the elderly using variables representative of the relationship between the trailing foot and an obstacle. [Subjects] Ten healthy elderly participants, who lived in C city, (age: 77.15±5.21 yrs, height: 149.87±3.54 cm, body mass: 57.44 ±6.74, and BMI: 25.58±2.98 kg/m2), participated in this study. [Methods] To determine the effect of 12 weeks’ aquatic training, 3-D motion analysis with 7 infrared ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
(19 reference statements)
0
8
0
3
Order By: Relevance
“…Although various short-term exercise modalities have been shown to improve obstacle avoidance during gait in elderly individuals [1][2][3][4], it remains unclear whether or not a long-term active lifestyle can provide similar benefits. Obstacle avoidance success rates were higher following a 5-week exercise programme including a functionally oriented obstacle course, walking and fall techniques [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although various short-term exercise modalities have been shown to improve obstacle avoidance during gait in elderly individuals [1][2][3][4], it remains unclear whether or not a long-term active lifestyle can provide similar benefits. Obstacle avoidance success rates were higher following a 5-week exercise programme including a functionally oriented obstacle course, walking and fall techniques [3].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because the experimental group only consisted of males and females in their 20s, the results cannot be generalized to all ages. The present results along with those of studies assessing resistance exercise for the elderly 26 ) , aerobic exercise 27 ) , aquatic exercise 28 ) , treadmill walking 29 ) , and muscular exhaustion recovery 30 ) are expanding the knowledge of the relationships of muscle groups with RPE.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, COP can be considered as a representative variable in gait analysis that influences older adults' functionality, as shown by Cadore et al (6), who reported an improvement in gait ability after a training period, as the average ability increased from 4% to 50%. Furthermore, other studies (41)(42)(43)(44)(45) have reported that in this population the risk of falls drops by up to 50% as there is less displacement of the COP during gait.…”
Section: Discussionmentioning
confidence: 71%